1997
DOI: 10.1074/jbc.272.40.25195
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns of Ca2+ Signals Define Intracellular Distribution of a Signaling by Ca2+/Calmodulin-dependent Protein Kinase II

Abstract: Cell signaling is the fundamental strategy by which cells respond to extracellular stimuli. Intracellular distribution of cell signaling is considered to be an important factor affecting the manner in which cells respond to extracellular stimuli with spatial specificity (1, 2). Although little is known of the spatial aspect of cell signaling, that of Ca 2ϩ signaling visualized by Ca 2ϩ microscopy is presently the best characterized example. Numbers of reports have shown that intracellular Ca 2ϩ signals occur l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Immunocytochemical studies using TM38 and TM71 revealed that these two sites were phosphorylated at the cleavage furrow during cytokinesis in U251 human glioma cells (Figure 1c and d). Together with previous immunocytochemical studies (Matsuoka et al, 1992;Tsujimura et al, 1994;Ogawara et al, 1995;Takai et al, 1996;Sekimata et al, 1996;Inagaki et al, 1997b) (Table 1).…”
supporting
confidence: 78%
“…Immunocytochemical studies using TM38 and TM71 revealed that these two sites were phosphorylated at the cleavage furrow during cytokinesis in U251 human glioma cells (Figure 1c and d). Together with previous immunocytochemical studies (Matsuoka et al, 1992;Tsujimura et al, 1994;Ogawara et al, 1995;Takai et al, 1996;Sekimata et al, 1996;Inagaki et al, 1997b) (Table 1).…”
supporting
confidence: 78%
“…Intermediate filaments enmesh the nucleus, and play a role in maintenance of nuclearcytoplasmic pathways. Cytoskeletal proteins are involved in protein kinase C and Ca 2+ /calmodulin-dependent protein kinase II signalling pathways that involve phosphorylation of intermediate filaments (Ogawara et al, 1995;Inagaki et al, 1997). Additionally, it was shown that cGMP-and cAMP-dependent protein kinases (Lamb et al, 1989;Wyatt et al, 1991) can also be involved in phosphorylation of intermediate filaments following their rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…To assess proliferative activity of cells associated with the metaplastic lesions, we used phosphorylated histone 3-specific antibodies, which recognize nuclei of mitotic cells (Hendzel et al, 1997;Inagaki et al, 1997;Preuss et al, 2003). At 7 months post infection, a large proportion of cells closely associated with the typical clusters of cytokeratin 6-postive cells displayed prominent nuclear histone 3 staining (Figure 3b).…”
Section: Chronic Mtb Infection Causes Squamous Cell Carcinomamentioning
confidence: 99%